Inovasi Pemasaran Produk Pupuk AB Mix untuk Mendorong Kewirausahaan Petani Milenial Kota Palangka Raya - Umi Novita Fitriah; Hastin Ernawati Nur Chusnul Chotimah; Fadhila Aziz; Wijantri Kusumadati; Marsa Priandini Leluni; Enos Jolian Patrio; Muhamad Abdul Rahman (Abdibaraya, 2026)
This Community Service Program aimed to enhance the entrepreneurial capacity of millennial farmers through marketing innovation of AB Mix fertilizer products in Palangka Raya City. The main problems faced by partners included limited access to AB Mix fertilizer, low independent production capability, and suboptimal digital-based marketing strategies. The methods applied consisted of assistance in AB Mix fertilizer production, training on packaging design and product legality, and digital marketing training using social media and online marketplaces. The results of the activity showed an increase in partners' knowledge and skills in producing AB Mix fertilizer, as assessed by pre-test and post-test results with an achievement rate of 97.27%. Furthermore, partners' understanding of innovation and marketing strategies for hydroponic businesses increased to 96.10%. The tangible impact of this initiative is evident in the expansion of market reach, which is no longer conventional but has now penetrated digital platforms through the creation of online stores and marketing content that enhances product competitiveness. This program contributes to encouraging millennial farmers to act not only as hydroponic vegetable producers but also as agribusiness entrepreneurs capable of independently and sustainably marketing innovative products